Psychologists’ experiences with telepsychology: qualitative analysis employing GDEISST framework - Al-Mahrouqi, Tamadhir; Al-Sharbati, Zena M.; Al-Alawi, Kamila; AlHarthi, Ahmed; Al Siyabi, Asayel; Al-Alawi, Mohammed; Al Humimia, Shaima; Al Salmi, Muna; Al-Hashemi, Tharaya; Al Nuumani, Rahma; Al Balushi, Fatma; Al Sinawi, Hamed (Frontiers in Digital Health, 2025)
ObjectiveTo explore Omani psychologists’ perceptions and experiences of telephone-based psychotherapy consultations, specifically regarding service quality, accessibility, and acceptability.MethodsAn exploratory qualitative study was conducted at Al Masarra Hospital in Muscat, Oman, between December 1 and 31, 2024. Five psychologists who provided telephone-based consultations were purposively sampled and participated in semi-structured, face-to-face interviews guided by the first three domains of the GDEISST framework (quality of services, accessibility, and acceptability). The acronym GDEISST stands for the “Guide for the Design, Evaluation, and Implementation of Telemedicine-Based Health Services.” Data analysis was conducted using inductive thematic analysis, while being guided by the first three domains of the GDEISST framework.ResultsTelephone-based psychotherapy quality is optimized by adopting a hybrid model after in-person sessions to establish trust and using clear, intentional communication supported by formal guidelines and training to compensate for lost non-verbal cues. Accessibility is hindered by client-side factors (privacy, scheduling, connectivity) and institutional constraints (limited phone lines, private spaces, and trained personnel). Finally, telephone consultations are broadly acceptable, particularly for clinically stable or stigma-sensitive clients, who appreciate the convenience and discretion they offer, but are considered unsuitable for high-risk cases such as active psychosis or suicidal ideation.ConclusionTelephone-based psychotherapy is viewed by Omani psychologists as a valuable adjunct to traditional care, enhancing access, reducing stigma, and supporting maintenance of stable clients provided that hybrid models (initial face-to-face engagement), structured training, and robust infrastructure are in place. However, high-risk or acutely unwell clients require in-person evaluation to ensure safety and treatment efficacy.